SP1.1.4 Caveat Chirurgicus - Opioid use following surgery. (9th August 2022) - Vijayagopal, Kesav Aditya; Majeed, Talal; Wilson, Jeremy; Magee, Conor
Abstract: Introduction: Over the last 20-years there has been increasing opioid related deaths, in the context of a worldwide epidemic of misuse including addiction and overdose. Startlingly, opioid commencement is usually iatrogenic. Most published data is from the USA with little evidence from UK surgical practice. Methods: Retrospective analysis of surgical unit opioid prescriptions. Data included opioids prescribed on discharge, 1, 3- and 6-months post-discharge usage and milligrams-of-morphine equivalence(mgEq) used to compare regimes. Results: One hundred cases reviewed. 35% of patients were opioid naïve on admission and of these 20%, 5.71% and 8.57% remained on opioids at 1, 3- and 6-months post discharge respectively. Females more likely to remain on long-term opioids at 6 months at lower doses (42% v 30%). Only 6% of discharge summaries recommended GP follow-up and assessment of opioid requirements. Furthermore, none were prescribed a tapering dosage regime on-discharge. Patients receiving Acute Pain Team reviews, more likely to remain on long-term opioids, at lower doses (30.67mgEq, 29.25mgEq and 32.63mgEq at 1-, 3- and 6-months post-discharge) compared to those without (69.16mgEq, 74.25mgEq and 65.13mgEq). Only 11% of patients with pre-existing opioid prescriptions were reviewed by the acute pain team. Worryingly, no documented assessment of opioid misuse risk in patients. Conclusion: Standardised assessments i.e., opioid Risk Assessment Tools and mgEq need to be documented and monitored in primary and tertiary care. Acute pain team services should be offered to more patients. Our study hopes to raise awareness of the need for effective opioid stewardship in surgical patients.